Hubungan Terpaan Iklan Situs Belanja Online LAZADA di Televisi dengan Minat Beli Masyarakat Kota Denpasar - Devi Redana, Ni Putu Saraswati; Amanda Gelgel, Ni Made Ras; Pradipta, Ade Devia (E-Jurnal Medium, 2017)
The advancement of technology and people’s desires to obtain items instantly, has made online-based business began to spread. LAZADA is one of the e-commerce site and startup with the biggest funding value in Southeast Asia. To increase sales, online shopping site can be often found in advertising world. Although there are many mass media channel, television is still the first choice to adverties many companies’s products. The purpose of this study is to find out the relation between LAZADA’s advertising exposure in television with the purchase interest of Denpasar’s citizen. This research used positivism paradigm, with asociatif descriptive quantitative approach. Sample were selected by nonprobability purposive sampling technique, and data were obtained by distributing questionnaires. The several stages of analyzing techniques used in this research are statistical data analysis techniques of frequency distribution, cross tabulation with data processing using SPSS program computational calculation and conclusions drawing. The results showed that there is a relation between LAZADA’s advertising exposure in television with the purchase interest of denpasar’s citizen. The relation of the two variable can be considered in the same direction, it means more often people exposed to LAZADA’s advertisement in television, the higher their purchase interest are. Kata Kunci:Advertising Exposure, LAZADA, Purchase Interest, Television.